Bone Marrow Mesenchymal Stem Cells (BMSCs) Restore Functional Endometrium in the Rat Model for Severe Asherman Syndrome. (March 2019) - Gao, Lufen; Huang, Zhongwei; Lin, Haiyingjie; Tian, Yuke; Li, Ping; Lin, Shaoqiang
Objective: To investigate the feasibility to restore functional endometrium using bone marrow mesenchymal stem cells (BMSCs) in the Sprague Dawley (SD["SD" has been defined as both "Sprague Dawley" and "standard deviation." Please clarify which one is to be followed.]) rat model for Asherman syndrome (AS). Design: Basic research on treatment of AS utilizing an optimized rat model. Setting: University research laboratories. Animal(s): Sprague Dawley rat model in which AS was induced in accordance to an optimized protocol. Intervention(s): Bone marrow mesenchymal stem cells were harvested from the rat's bone marrow and labeled with green fluorescent protein (GFP) in the second passage of BMSCs. The fifth passage of GFP-labeled BMSCs was injected systemically through the tail vein in the optimized AS rat model. Main Outcome Measure(s): We examined the reproliferation of the endometrial lining and the expression of markers for endometrium and endometrial receptivity. The localization of engrafted GFP-labeled BMSCs was determined by a laser scanning confocal microscope and a fluorescence microscope. The number of pregnant rats and implanted embryos in each uterus was recorded to evaluate the function of endometrium. Result(s): We had demonstrated that in the in vivo experiments on our rat model for AS, the group which received BMSC injection had significantly improved reproductive outcomes—70% of these rats conceived, whereas none of the rats in the control group got pregnant ( P < .01, χ 2 test). The mean number of embryos undergoing implantation was 14 ± 1.24 in the sham group and 7 ± 5.70 in the BMSC group (Levene test, P = .001). There was no significant difference between the groups from the time of coitus to conception. To further determine how BMSC injection could have resulted in the improved reproductive outcomes in rats with AS, we employed immunohistochemical techniques to examine the endometrium of these treated rats. On hematoxylin-eosin staining, we noted the reproliferation of all layers of the endometrium and with Masson staining, we noted significant reduction in fibrosis in the damaged endometrium of rats treated with BMSCs. Counterstaining for GFP and cytokeratin-positive cells was noted in the endometrial lining of treated rats, which might suggest the action of BMSCs in regenerating the damaged endometrial lining. The expression of the endometrial receptivity marker, Leukemia inhibitory factor (LIF), in this regenerated endometrial lining could have resulted in the improved reproductive outcomes observed in the AS rat model treated with BMSCs. Conclusion: Bone marrow mesenchymal stem cells were likely to play an important role in the reconstruction of the injured endometrium and improvement of reproductive outcomes in the optimized AS rat model.